2014
DOI: 10.1186/1556-276x-9-513
|View full text |Cite
|
Sign up to set email alerts
|

A versatile chemical conversion synthesis of Cu2S nanotubes and the photovoltaic activities for dye-sensitized solar cell

Abstract: A versatile, low-temperature, and low-cost chemical conversion synthesis has been developed to prepare copper sulfide (Cu2S) nanotubes. The successful chemical conversion from ZnS nanotubes to Cu2S ones profits by the large difference in solubility between ZnS and Cu2S. The morphology, structure, and composition of the yielded products have been examined by field-emission scanning electron microscopy, transmission electron microscopy, and X-ray diffraction measurements. We have further successfully employed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(13 citation statements)
references
References 44 publications
1
12
0
Order By: Relevance
“…The Raman peaks at 295 and 588 cm –1 correspond to first order (1-LO) and second order (2-LO) modes of CdS, respectively. The slight blue shift observed in Figure S4b is attributed to the change in the crystalline size. , The characteristic peak attributed to Cu 2 S at around 472 cm –1 is not detected, , further indicating the successful Cu + doping.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…The Raman peaks at 295 and 588 cm –1 correspond to first order (1-LO) and second order (2-LO) modes of CdS, respectively. The slight blue shift observed in Figure S4b is attributed to the change in the crystalline size. , The characteristic peak attributed to Cu 2 S at around 472 cm –1 is not detected, , further indicating the successful Cu + doping.…”
Section: Resultsmentioning
confidence: 91%
“…The slight blue shift observed in Figure S4b is attributed to the change in the crystalline size. 25,39 The characteristic peak attributed to Cu 2 S at around 472 cm −1 is not detected, 40,41 further indicating the successful Cu + doping. The photocatalytic activities for hydrogen production of the as-prepared C-Cu-CdS PNs with different concentrations of Cu + doping were evaluated by using 0.25 M Na 2 SO 3 and 0.35 M Na 2 S as hole scavengers in 100 mL of distilled water irradiated with visible light (λ > 420 nm).…”
Section: ■ Experimental Sectionmentioning
confidence: 97%
“…Chang et al also demonstrated that Cu-rich CIS provided excellent performance as CEs for the iodide electrolyte in DSSCs . Shuai et al produced Cu 2 S nanotubes, by cation exchange of ZnS nanotubes, and demonstrated their relatively good performance as CE in DSSCs with the iodine electrolyte, reaching PCEs up to 2.88% . Chen et al.…”
Section: Photovoltaic Applicationsmentioning
confidence: 99%
“…16 As an extended solar cell application, Cu 2 S has also been employed in the fabrication of quantum dot sensitized (QDSSC) or dye sensitized solar cells (DSSC). [138][139][140][141] It is a well-known fact that noble metals such as Pt, Au are widely accepted as counter electrodes in the TiO 2 -based QDSSCs and DSSCs. However, the chemisorption of electrolyte on metal catalysts causes high overpotential leading to low fill factor.…”
Section: Solar Cellsmentioning
confidence: 99%